The Application of Information Technology in Libraries in VietNam and Requirements for Organisational Models, Conference: “Asian, Aspirations: Libraries for Sustainable Advancement” - Nguyễn, Văn Thiên (Congress of Southeast Asian Librarians, 2020)
There are many factors that affect the performance of and management is the most important factor. This is because a suitable organizational model together with methodological and scientific management mechanism will bring enormous benefits such as saving money, time, labor power while minimizing physical damage and loss, increasing productivity and creating the most effective in operation. In recent decades, libraries in Vietnam have gained significant development thanks to the innovation policy of the Party and Government. A large number of libraries in Vietnam is transforming from traditional libraries to modern libraries. Information technology and emerging technologies have fundamentally changed professional procedures and business processes as they have been automated. Such a change brings in many benefits to users and libraries. However, this also causes many shortcomings in library management because the majority of the current organizational models utilized in libraries are traditional. This article analyzes changes in Vietnamese libraries and requirements for their organizational models